"Tandem-action" ferrocenyl iodocuprates promoting low temperature hypergolic ignitions of "green" EIL–H2O2 bipropellants. Issue 29 (16th July 2020) - Wang, Kangcai; Liu, Tianlin; Jin, Yunhe; Huang, Shi; Petrutik, Natan; Shem-Tov, Daniel; Yan, Qi-Long; Gozin, Michael; Zhang, Qinghua
Abstract : The fast auto-ignition of energetic ionic liquid fuels with H2 O2 was achieved under low temperature conditions by using new promoters, paving the way for the development of green bipropellants. Abstract : The combination of Energetic Ionic Liquid (EIL) "green" fuels and high test peroxide (>90% H2 O2 ; HTP), as a "green" oxidizer, is a very promising platform for the development of fully "green" bipropellants for space exploration. In this work, two new "tandem-action" promoters – [FcCH2 N(CH3 )3 + ]2 [Cu2 I4 2− ] (P1 ) and [FcCH2 N(CH3 )3 + ] n [Cu2 I3 − ] n (P2 ) – and two reference "single-action" promoters, [FcCH2 N(CH3 )3 + ][H3 BCN − ] (P3 ) and [CH3 N(CH2 CH3 )3 + ] n [Cu2 I3 − ] n (P4 ), were prepared, comprehensively characterized and evaluated for their ability to significantly shorten the Ignition Delay (ID) times of hypergolic reactions between a series of EILs and H2 O2 . These promoters exhibited high solubility and long-term chemical stability in a typical EIL fuel – 1-ethyl-3-methylimidazolium dicyanamide (F1 ). Upon screening the performance of promoter–EIL formulations, the best ID result of 31 ms was observed for the combination of 1-ethyl-3-methylimidazolium cyanoborohydride (F2 ) fuel and promoter P2 (10 wt%), with H2 O2 (95%), whereas an ID time of 58 ms was observed for the F2 /P2 formulation with commercially available H2 O2 (70%), respectively. Remarkably, the latter formulation remained fully homogeneous even at −40 °C, and showed an ID time of 66 ms at this temperature with H2 O2 (95%), indicating the advantages of our approach for the development of novel fully "green" bipropellants.